LEMBAGA PENYELENGGARA PEMILIHAN UMUM DI INDONESIA: BERBAGAI PERMASALAHANNYA - Indra Pahlevi (Sekretariat Jenderal DPR RI, 2011)
As Indonesia is a democratic state, general election is a means to run the people sovereignity. To achieve a qualified election, we need a proffesional institution there on. Such a professional institurion has been conducted by the Constitution 1945, Article 22E section (5) as saying that the election is held by a national election commission, whics is permanent and autonom. The provision underlines that such an institution shall be free from any form of intervention and from whatever parties, in conducting its all tasks, function and authorities. Today there has been the law No. 22/2007 on The Election Organizer ruling the National Election Commission, Election Oversight Body and its their function and authorities. However, refering to the evaluation of the election in 2009, there have been many problem arising from organizing, tentative eligible voters, the seats allocation to the determination for the elected legislators. The main reason for such problems count for both doubtedness of the integrity and capacity of the commissioners and unsincronized electoral legal frameworks. Therefore, there shall be a concrete effort to organise an election through a more comprehensive codified legal frameworks. Partial amandement of the Law No. 22/2007 shall be viewed as an intervening goal to achieve a comprehensive electoral legal frameworks.